Inefficiency in the German mechanical engineering sector - Alexander Schiersch (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper aims to examine the relative efficiency of German engineering firms using a sample of roughly 23,000 observations between 1995 and 2004. As these firms had been successful in the examination period in terms of output- and export-growth, it is expected that a majority of firms is operating quite efficiently and that the density of efficiency scores is skewed to the left. Moreover, as the German engineering industry is dominated by medium sized firms, the question arises whether these firms are the most efficient ones. Finally an increasing efficiency gap between size classes over time is important since that would be a signal for a structural problem within the industry. The analysis - using recently developed DEA methods like bootstrapping or outlier detection - contradicts the two first expectations. The firms proved to operate quite inefficiently with an overall mean of 0.69, and efficiency differs significantly with firm size whereas medium sized firms being on average the least efficient ones. When looking at changes in efficiency over time, we find a decreasing efficiency gap between size classes.
Keywords: C14; L60; 330; DEA; German engineering firms; Maschinenbau; Wirtschaftliche Effizienz; Betriebsgrößenstruktur; Data-Envelopment-Analyse; Deutschland